Reader's Culture in A Modern School: Problems, Solutions - Navruzova Elena Pavlovna (Periodica Journal, 2022)
This article examines the problem of the reader's interest of modern schoolchildren and parents at the moment, as well as the role of literature in the development and formation of students' emotional and creative abilities. The essence of the concept of "reader's culture" is revealed
Keywords: information; literacy; love; interest